Conceptual analysis of social responsibility of the person and its integration in pharmaceutical practice - N. O. Tkachenko; В. Р. Hromovyk (Zaporozhye State Medical University, 2017)
The modern development of the social policy of pharmaceutical organizations in Ukraine, focused on the needs of society, is characterized by the lag in practical implementation of appropriate social responsibility (SR) from the increased interest of pharmaceutical scientists in its various aspects. Issues of personal identity, its role and place in the system of socially responsible behavior of pharmaceutical organizations and the professional activity of pharmacists remain insufficiently studied. The purpose research. Conceptual analysis of the social responsibility of the individual with the integration into pharmacy and the rationale for strategic directions for the formation of social responsibility as a professional competence of pharmacists in the system of continuous pharmaceutical education. Materials and methods. We used the methods of information retrieval, comparison, systematization, analysis, synthesis and modeling. Materials for research were publications of fundamental and applied research of domestic and foreign scientists on issues of social responsibility, international standards. Results. Personality in the process of activity is both the subject and the object of responsibility, since social responsibility is a condition for interaction between the individual and the society. The social responsibility of pharmacy specialists directed to primary and secondary social groups, society and the individual, as well as to oneself. In the latter case, the self-concept is important, that is, the individual's complete self-image and the readiness of the individual to act in a certain way in certain situations, as well as the possible social roles of the pharmacist. The process of forming the social responsibility of pharmacy specialists is a complex level system that continuously educates, develops and improves the skill of social responsibility throughout professional life. Conclusions. On the basis of theoretical generalization of the scientific literature a conceptual analysis of fundamental level of social responsibility with the integration in a theoretical plane of pharmaceutical practice was carried out. We also justified our own definition of the social responsibility of a pharmacist. By modeling it is determined that the formation of the social responsibility of a specialist pharmacy occurs throughout his professional life. The sources of development of SR are the state, subjects of pharmaceutical business, subjects of pharmaceutical education and science, public organizations of the pharmaceutical sector, the pharmacist himself. All this determines the multi-vector nature and variety of means of forming its social responsibility.